The prevalence of metabolic syndrome in pre- and post-menopausal women attending a tertiary clinic in Turkey - YOLDEMİR, AHMET TEVFİK (ELSEVIER SCIENCE BV, 2012)
Objective: To determine the prevalence of metabolic syndrome among pre- and post-menopausal women attending a tertiary clinic in Turkey. Study design: This is a cross-sectional study consisting of one hundred and eighty healthy postmenopausal women and fifty-three healthy premenopausal women evaluated for presence or absence of metabolic syndrome. The t test and Fischer exact test were used for continuous variables and chi-square test was used for categorical variables. Results: The prevalence of metabolic syndrome among pre-menopausal women was 15.09% according to NCEP criteria. The prevalence of metabolic syndrome among postmenopausal women was 19.44% according to NCEP criteria. There was no significant difference in the prevalence of metabolic syndrome between premenopausal and postmenopausal women in our study population. Conclusion: There was no significant difference in the prevalence of metabolic syndrome between premenopausal and postmenopausal women attending a tertiary clinic in Turkey. (C) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: Postmenopause; Pre-menopause; Prevalence; Metabolic syndrome; CORONARY-HEART-DISEASE; CARDIOVASCULAR-DISEASE; MENOPAUSAL TRANSITION; RISK PROFILE; SERUM-LIPIDS; BODY-FAT; ASSOCIATION; MORTALITY; FRAMINGHAM; OBESITY